Insights from the CGIAR Science Forum 2011: Brief 41 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
This brief highlights the key insights from the 2011 Science Forum to help guide future decisions within the CGIAR.